Projeto de lajes treliçadas unidirecionais: comparação entre os cálculos manuais, programa comercial de cálculo e projeto existente - Laio, Douglas Calazans (Brasil, 2022)
With the growth of the population and the construction industry the demand for new residences, either multifamily or single-family, is also growing. This research discusses the sizing and comparison of manual calculations, the commercial program CypeCad®, and the executive project of the building analyzed, of a type of slab system widely used in Brazil in the construction of small and medium sized residential buildings, the truss slab system. It can be concluded that the analysis of the structure performed by the commercial program differs from the values obtained by manual sizing, as well as the area of steel used in the executive project, which resulted on different values from those calculated manually, according to the current regulations for truss slab structures. In summary, the manual calculation was the most conservative of the three proposals analyzed, regarding bending moments, the vertical deformations in the slabs, and also the additional reinforcement in the truss.